Alain Peyrefitte. Cuando China despierte... el mundo temblará —ojeada sobre la ruta china— Barcelona. Plaza Janes, S.A., Editores, 1977. pp. 621. - Pinheiro C., Juárez (Estudios de Asia y África, 1981)
-